Program Pembelajaran Harian (RPPH) Berbasis Keterampilan Berpikir Tingkat Tinggi Di Lingkungan Guru Paud Kecamatan - Kurniah, Nina; Agustriana, Nesna (Yayasan Darussalam Bengkulu, 2023)
The implementation of curriculum development, especially in PAUD, consists of semester programs, weekly programs and daily programs called (Daily Learning Development Plans (RPPH). The purpose of this activity is to improve teachers' knowledge and skills in developing HOTS-based RPPH. Community service activities were carried out at Alfajar PAUD located at Z. Arifin, Singaran Pati District, Bengkulu City and attended by 23 teachers from representatives of 15 PAUDs in the Singaran Pati Cluster. The activity methods that will be carried out are, 1) Teachers are given classical material on what, why and how to develop HOTS-based RPPH, 2) In-depth discussion of the material presented by holding questions and answers so that the material discussed is properly understood by the training participants, 3) Group work to create and discuss HOTS-based RPPH, 4) Presenting the results of the work, while evaluating the achievement of objectives, 5) Revising the results of the work based on the input provided and the overall discussion, and 6) Producing a final document, namely HOTS-based RPPH which is ready to be implemented. The results of this activity were that teachers were able to develop learning tools in the form of RPPH (Research Plans for Daily Learning) plans. This will impact teachers' skills in developing learning tools in the form of HOTS-based Daily Learning Plans (RPPH) for meaningful learning activities for students. This Community Service activity was well-implemented and ran smoothly according to the pre-planned activity plan. Training participants mastered the material presented, enabling them to develop HOTS-based learning tools.